VALIDITY AND RELIABILITY STUDY OF ATTITUDE SCALE FOR PLANNING INSTRUCTION (Third Sector Social Economic Review, 2019)
In this study, it is aimed to develop a measurement tool which has the reliability and validity of measurement to be used to determine the attitudes of prospective teachers towards planning instruction. 46-item attitude scale trial form for instruction planning which was created in compliance with the process of creating scale items was applied to 524 senior year students in their 2018-2019 academic year, studying in different teaching programs of Gazi University, Gazi Education Faculty.In the determination of the study group, it was taken into consideration that the attitudes of the prospective teachers about the planning instruction will be clarified in their final year. By carrying out validity and reliability analyzes on the data obtained from the application performed to the prospective teachers, evidence on the psychometric properties of the scale form was obtained.  Exploratory Factor Analysis (EFA) was performed for the construct validity through the data set  obtained from half of the study group and Confirmatory Factor Analysis (CFA) was performed on the data set obtained from the other half. According to the results of Exploratory Factor Analysis (EFA), it was determined that the scale consisted of 37 items and 3 sub-dimensions. Scale sub-dimensions were named as follows, based on the judgments reflected by the scale items: ""Belief in the Benefit of Planning"", ""Negative Belief in Planning"", and ""Finding Planning Important"". It was determined that the three-factor structure related to the scale explained 50.91% of the total variance. The Cronbach alpha coefficient was 95 for the whole scale for the subscales of the scale was 92, 90 and 89, respectively. The results obtained from the confirmatory factor analysis revealed that the 3-factor structure was confirmed. These findings suggest that the scale is a valid and reliable measurement tool to determine attitudes towards planning instruction.
Keywords: Planning of Instruction; Attitude Towards Planning Instruction; Developing Attitude Scale